In pursuit of the Almighty's dollar : a history of money and American Protestantism - Hudnut-Beumler, James David (University of North Carolina Press, 2007)
In a fascinating look into the economics of American Protestantism, Hudnut-Beumler examines how churches have raised and spent money from colonial times to the present and considers what these practices say about both religion and American culture. He contends that paying for earthly good works done in the name of God has proved highly compatible with American ideas of enterprise, materialism, and individualism. The financial choices Protestants have made throughout history--how money was given, expended, or even withheld--have reflected changing conceptions of what the religious enterprise is.